Medicolegal and Cultural Anthropological Aspects of Tattooing: a Qualitative Atudy - Hulathduwa, S. R.; Ariyarathna, H. T. D. W. (My University, 2019)
Mummified human skins and ancient art containing tattoos, tools used for tattooing etc. prove that tattooing had been in practice since at-least 4000 BC. Tattooing is a form of permanent body modification. Body modifications could be permanent or temporary. Body painting is the commonest form of temporary body modification. Permanent modifications include tattooing, piercing, branding and prosthesis. Branding is a disfiguring, incriminating practice usually not accepted cosmetically. Tattooing is a science and an art evolving with human culture. The account that the authors wish to discuss is based on the working experience of three countries Australia, UK and Sri Lanka during the past seven years. Some important points are summarized below accordingly. The nature of tattoos differs from culture to culture. It is dynamic and evolves in the same culture with time. Conventional tattoos (barb wire, snake and dagger, cross, “Amma Buduwewa”, “Maruwa Samage Wase” etc.) are diminishing. The culture of tattooing is gaining rapid popularity and acceptance in all communities. Tattoos are still commoner among the lower socio-economic classes though this disparity is rapidly diminishing. Some are black while others are bi or tri-chromatic. Tattoos are becoming popular among females. There are gender differences in tattoos. Tattoos act as a rich source of information as to the barer’s ethnicity, language, religious faiths, preferences (sexual or otherwise), personal data and socio-cultural background. Some such information is misleading at times. Forensically, tattoos help establishing specific identity of the living and the dead. Tattoos become prominent in early putrefaction. Historical forensic evidence that drug peddlers tend to tattoo No 13 in their lower lips and gays tattoo a blue-bird in the web between thumb and fore-finger are still valid. Some individuals bare extremely unusual tattoos. Others bare tattoos on unusual sites of their anatomy such as on the penis and around anal verge. Some use tattoos to hide old scars, moulds, previous ugly tattoos and recreational drug injecting sites. Crude attempts of removing tattoos are always obvious while laser quarterization is less disfiguring. Some tattoos become culturally unacceptable when the person grows old. Tattooing is generally considered as posing a risk of contracting blood-borne infections on the person.
Keywords: body modifications, tattooing, identification, forensic (evidence)